SECURITY STRATEGIES AND INVOLVEMENT IN EFFORTS TO PREVENT SMUGGLING OF ILLEGAL GOODS AT CIKARANG CLASS IIA PENITENTIARY - Layola, Igantius; Jarodi, Odi (Universitas Nusa Cendana, 2025)
This study examines the significant challenges and strategic approaches for preventing the smuggling of contraband, particularly mobile phones, within Class IIA Cikarang Prison. Utilizing a qualitative research design alongside a SWOT analysis, the study identifies both internal and external factors that impact the effectiveness of security systems in correctional facilities. The findings reveal that key elements such as comprehensive training and the development of human resource capacity, the provision of adequate security equipment, and enhanced collaboration with law enforcement and related agencies are essential for bolstering smuggling prevention efforts. The research emphasizes the importance of a well-trained security workforce that is knowledgeable about illegal items and equipped with the necessary tools, such as metal detectors and surveillance systems. Recommendations stemming from the study include upgrading prison facilities to meet contemporary security standards, implementing continuous training programs for personnel to keep them informed about the latest smuggling techniques, and enforcing stricter disciplinary measures for staff who fail to fulfill their responsibilities. By addressing these areas, Class IIA Cikarang Prison can improve its overall security framework and mitigate the risks associated with contraband smuggling, ultimately enhancing safety within the facility. Keywords : Prevention; Smuggling; Class IIA Cikarang Prison